2009
DOI: 10.1073/pnas.0803665106
|View full text |Cite
|
Sign up to set email alerts
|

A DNA damage response in Escherichia coli involving the alternative sigma factor, RpoS

Abstract: We isolated an Escherichia coli mutant in the iraD gene, sensitive to various forms of DNA damage. Our data are consistent with the function of IraD to promote accumulation of the alternative transcription sigma factor, RpoS, by binding to the adaptor RssB protein that targets RpoS for degradation. Our results demonstrate the physiological importance of this mode of regulation for DNA damage tolerance. Although RpoS is best known for its regulation of genes induced in stationary phase, our work underscores the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 37 publications
4
82
0
1
Order By: Relevance
“…IraP and IraD are normally present in the cell at low levels; their synthesis increases enough to stabilize RpoS only under specific stress conditions (2,4,18). The fact that IraP and IraD stabilize RpoS in an aceE::kan mutant suggests that their expression is induced in this background.…”
Section: Rpos Stabilization In the Acee Mutant Is Dependent Upon Indumentioning
confidence: 99%
See 1 more Smart Citation
“…IraP and IraD are normally present in the cell at low levels; their synthesis increases enough to stabilize RpoS only under specific stress conditions (2,4,18). The fact that IraP and IraD stabilize RpoS in an aceE::kan mutant suggests that their expression is induced in this background.…”
Section: Rpos Stabilization In the Acee Mutant Is Dependent Upon Indumentioning
confidence: 99%
“…IraM, induced via activation of the PhoQ/PhoP two-component system, is similarly critical for RpoS stabilization during low Mg 2+ growth (2). IraD induction is not fully understood, but it clearly plays a role both in the transition to stationary phase, via induction of a ppGpp-dependent promoter, and after DNA damage (4,5). IraM and IraD are also negatively regulated by H-NS (6).…”
mentioning
confidence: 99%
“…Accordingly, we conclude that phosphorylation of SprE is not integral to the carbon starvation signaling pathway that regulates RpoS. SprE was recently found to regulate mRNA stability (Carabetta et al 2009), and it is not known if phosphorylation plays a role in that activity.In response to other stresses, such as phosphate starvation, magnesium starvation, and DNA damage, a major mechanism for RpoS accumulation is antagonism of the adaptor SprE by the anti-adaptor proteins IraP, IraM, and IraD, respectively (Bougdour et al 2006(Bougdour et al , 2008Merrikh et al 2009). However, none of the Ira proteins have been associated with carbon starvation, and despite extensive screens, no other proteins have been identified in the carbon starvation signaling pathway.…”
mentioning
confidence: 99%
“…In response to other stresses, such as phosphate starvation, magnesium starvation, and DNA damage, a major mechanism for RpoS accumulation is antagonism of the adaptor SprE by the anti-adaptor proteins IraP, IraM, and IraD, respectively (Bougdour et al 2006(Bougdour et al , 2008Merrikh et al 2009). However, none of the Ira proteins have been associated with carbon starvation, and despite extensive screens, no other proteins have been identified in the carbon starvation signaling pathway.…”
mentioning
confidence: 99%
“…It was reported that an engineered sigma factor library could reprogram metabolic flux and thus led to diverse phenotypes, and some of mutant strains could be used for industrial production purposes [12]. Additionally, sigma factors were shown to be associated with the cell survival under stress conditions [13][14][15]. Based on above information, we speculated that sigma factors may affect promoter activity.…”
Section: Introductionmentioning
confidence: 86%